2013
DOI: 10.1159/000354116
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Vildagliptin on Retinal Injury in Obese Type 2 Diabetic Rats

Abstract: Background/Aims: Vildagliptin is an oral inhibitor of dipeptidyl peptidase-4, an enzyme mainly responsible for inactivating incretins, and one of the widely used drugs for the treatment of type 2 diabetes. However, effects of vildagliptin on retinal injury in diabetes remain unclear. We examined here whether oral administration of vildagliptin inhibited gene expression of inflammatory and thrombogenic parameters in Otsuka Long-Evans Tokushima Fatty rats (OLETF rats), an animal model of obese type 2 diabetes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The experimental evidence on the effects of the oral administration of DPP-IVi in diabetic retinopathy is limited and controversial [29][30][31][32]. Gonçalves et al [29] showed that sitagliptin prevented changes in the endothelial distribution of tight junction proteins and decreased nitrosative stress, the inflammatory state and cell death by apoptosis in Zucker Diabetic Fatty (ZDF) rats (a rat model of type 2 diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental evidence on the effects of the oral administration of DPP-IVi in diabetic retinopathy is limited and controversial [29][30][31][32]. Gonçalves et al [29] showed that sitagliptin prevented changes in the endothelial distribution of tight junction proteins and decreased nitrosative stress, the inflammatory state and cell death by apoptosis in Zucker Diabetic Fatty (ZDF) rats (a rat model of type 2 diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, vildagliptin has shown improved healing features for chronic foot ulcers in patients with T2DM [31]. Several pre-clinical studies also observed the importance of DPP-4 inhibitors in treating microvascular complications associated with diabetes [3235]. Most of the studies on humans investigating importance of DPP-4 inhibitors in microvascular complications were preliminary and short-term studies, and further large and long-term trials are required to corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diabetes mellitus and/or arterial hypertension, this reflex arc is impaired, most probably caused by deterioration in the release and metabolism of nitric oxide [15][16][17][18]. Beneficial effects of DPP-IV inhibition on blood pressure, retinal and renal function have been suggested in experimental studies [19][20][21] and in individuals with type 2 diabetes mellitus [10,11,22,23]. In our study, treatment with linagliptin improved retinal capillary perfusion, retinal arterial blood flow and the hyperemic response to flicker light in nondiabetic, hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%